Direct and Indirect Effects of Long-Term Field Warming Methods on the Physical Environment and Biological Responses in a Subtropical Forest - Wu, Ting; Tissue, David Thomas; Zhou, Guoyi; Yan, Junhua; Zheng, Mianhai; Li, Xu; Song, Yuting; Li, Yuelin; Tang, Xuli; Liu, Shizhong; Chu, Guowei; Meng, Ze; et al. (Frontiers in Forests and Global Change, 2022)
Tree growth may be affected by rising temperature. We conducted two long-term, independent warming experiments in a subtropical forest; one experiment used infra-red (IR) warming and one experiment used translocation warming. Both warming techniques are designed to increase air and soil temperatures (Tair and Tsoil), but may also differentially affect other environmental variables, including air relative humidity (RH), vapor pressure deficit (VPD) and soil volumetric water content (SVWC). Hence, tree response ascribed to Tair and Tsoil may be dependent on the indirect effects of the warming techniques. We experimentally tested these ideas on three native tree species (Machilus breviflora, Syzygium rehderianum and Schima superba), which occurred at all experimental sites, in subtropical China. IR warming was imposed at an experimental site in a monsoon evergreen broadleaf forest (+ 1.82 oC; 5 years). We translocated trees from higher elevation sites to lower elevation sites in the coniferous and broadleaf mixed forest (+ 0.68 oC; 8 years) and mountain evergreen broadleaf forest (+ 0.95 oC and + 1.63 oC; 8 years). We found that both methods directly increased Tair and Tsoil (although to varying degrees), while IR warming indirectly dried the air (lower RH and higher VPD) and translocation warming indirectly dried the soil (lower SVWC). Trees exposed to IR warming exhibited reduced photosynthesis due to lower RH (M. breviflora) and to lower stomatal conductance (gs) as a function of higher Tair (S. rehderianum and S. superba). M. breviflora exposed to translocation warming exhibited lower photosynthesis due to higher Tsoil and lower SVWC, leading to declining growth. Higher Tair and Tsoil due to translocation warming increased photosynthesis and growth for S. superba. This study highlights the potential direct and indirect effects of different warming techniques on the physical environment of forest ecosystems, and subsequently their impacts on biological traits of trees. Hence, different warming techniques may provide different outcomes when assessing the impact of warming on trees in future climates.